In-hospital Breastfeeding and Intention to Return to Work Influence Mothers' Breastfeeding Intentions. (November 2016) - Thomas-Jackson, Shera C.; Bentley, Gail E.; Keyton, Kristina; Reifman, Alan; Boylan, Mallory; Hart, Sybil L.
Background: Research continues to demonstrate that formula feeding is associated with numerous long-term negative outcomes for a mother and her infant. However, many women cease breastfeeding sooner than intended and recommended. Breastfeeding has been found to be related to demographics, maternal mood, and returning to work outside the home. Objectives: This study aimed to shed light on the woman's perception of the effect of working on intended breastfeeding duration. This study used intentions to return to work and in-hospital breastfeeding to predict breastfeeding intentions. Methods: Women (N = 160) were surveyed during the first 48 hours postdelivery of healthy, full-term infants. Survey instruments included demographics (socioeconomic status, maternal age, education, and marital status), depression, fetal attachment, current exclusive breastfeeding status, as well as breastfeeding and return-to-work intentions for the next year. A path analysis was used to explore relationships and predictors of breastfeeding intentions. Results: The model had a good fit and breastfeeding intentions were predicted by exclusive breastfeeding in the hospital (β = 0.21, P < .01) and negatively predicted by return to work (β = −0.18, P < .05). Conclusion: Exclusive breastfeeding in the hospital within the first 48 hours postpartum and intention to return to work influence how long a mother intends to breastfeed. Attention to these areas can be provided immediately postpartum to support exclusive breastfeeding and provide informational support on continuing to breastfeed/express milk upon return to work if the mother intends to return to work.